On the surging potential of polar ice streams : Antarctic surges, a clear and present danger? - Radok, Uwe; McInnes, Barry; Jenssen, Dick; United States. Dept. of Energy. Office of Basic Energy Sciences. Carbon Dioxide Research Division (Washington, D.C. : U.S. Dept. of Energy, Office of Energy Research, Office of Basic Energy Sciences, Carbon Dioxide Division, 1987)
Mode of access: Internet.